Voices of the Dead: Robert Eggers’s The Lighthouse and the Horror Genre - Morawiec, Maciej (Text Matters: A Journal of Literature, Theory and Culture, 2024)
This article examines the 2019 film The Lighthouse, directed by Robert Eggers, which follows the descent into madness of two 19th-century lighthouse keepers as they become stranded on a desolate New England island and confronted with threats both natural and supernatural. The focus of the article is primarily on the film’s employment of the cinematic language associated with the horror genre, discussed primarily in reference to the theoretical framework proposed by Noël Carroll, and thus it serves as the argument for The Lighthouse’s inclusion into the genre. I place particular emphasis on the considerations of human nature present in the film. The Lighthouse illustrates the disastrous impact of finding oneself outside of the boundaries of civilization; without the constraints imposed by society, but also without the sense of security it offers, the evil that can be found in every human being is revealed and the characters turn against each other.